Characterization And Screening Of Protease, Amylase, And Cellulase From Phylloplane Fungi Isolates Of Avicennia marina (Forssk.) Vierh. - Mahardhika, Wahyu Aji; Ramadhany, Warih; Lunggani, Arina Tri (Jurnal Biologi Universitas Andalas, 2021)
Mangrove (Avicennia marina) is an important mangrove species, because it has many benefits for human life, including in the ecological scope as a source of food and medicine. These plants can also be used as a source of symbiont mold isolates which can be developed as an alternative to produce bioactive compounds, one of which is enzymes. Enzymes are protein compounds that can catalyze all chemical reactions in biological systems. This study aims to determine whether mangrove symbiont fungi (A. marina) can produce amylase, protease and cellulase enzymes. This research was conducted using a method based on enzyme activity, namely amylase activity with lugol iodine staining, protease activity and cellulase activity with congo red staining. on agar media enriched with 1% skim milk, 1% starch and 1% CMC. The results showed that 4 isolates were able to show potential enzymatic activity to be developed as agents for enzyme production.